2019
DOI: 10.1002/ceat.201900316
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Steam Reforming Followed by Water‐Gas Shift Reaction over Ce‐Ni/MCM‐41 and Fe‐Based Catalysts

Abstract: Current research focuses on hydrogen production from ethanol steam reforming (ESR) followed by water-gas shift (WGS) reaction. Ce-Ni/MCM-41 and Fe/Ce/M (where M = K, La, Ti) catalysts were prepared by the wet-impregnation technique and used for the ESR and WGS reactions, respectively. All experiments were carried out at 600°C. The effects of the reduction time, the ratio of the two catalysts, and their arrangement were also investigated. The best results were obtained using Fe/Ce/Ti as WGS catalyst and with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…The strong interaction between CeO 2 and Ni species inhibits carbon deposition and the sintering of Ni particles, which in turn enhances the WGSR. [225][226][227] According to the previous reports, CeO 2 nano-rods (NR) expose the {100} and {110} facets, CeO 2 nano-cubes (NC) dominantly expose the {100} facets while the nano-particles (NP) preferentially expose both the {111} and {100} facets. [228] In view of the structure dissimilarity on different crystal planes, the redox properties and oxygen mobility of CeO 2 usually have a close connection with its morphology, which shows a significant effect on activation capacity for oxygenated species.…”
Section: Ceomentioning
confidence: 98%
“…The strong interaction between CeO 2 and Ni species inhibits carbon deposition and the sintering of Ni particles, which in turn enhances the WGSR. [225][226][227] According to the previous reports, CeO 2 nano-rods (NR) expose the {100} and {110} facets, CeO 2 nano-cubes (NC) dominantly expose the {100} facets while the nano-particles (NP) preferentially expose both the {111} and {100} facets. [228] In view of the structure dissimilarity on different crystal planes, the redox properties and oxygen mobility of CeO 2 usually have a close connection with its morphology, which shows a significant effect on activation capacity for oxygenated species.…”
Section: Ceomentioning
confidence: 98%
“…Various kinds of mesoporous SiO 2 have been used as supports due to their high surface area and connement effect. [76][77][78] Elharati et al compared SBA-15 and commercial SiO 2 as the support for Ni-Mo bimetallic SRE catalyst at 600 °C and atmospheric pressure. 79 The ordered mesoporous structure of SBA-15 as well as the high specic surface area ensures the high dispersion of NiMo, and the mesopores restrain carbon formation.…”
Section: The Effects Of Active Metalsmentioning
confidence: 99%
“…In previous studies, various types of catalyst systems were investigated for the MTS reaction 1. The results showed that cerium oxide (CeO 2 ) supports have been widely used in the MTS catalysts due to their good properties, such as the ability to accelerate the oxidation and reduction of oxygen, their storage capacity, and the easy mobility of the surface oxygen 12, 13. Furthermore, the Ni/CeO 2 catalysts have a high thermal conductivity that facilitates heat removal from exothermic reactions and can be used in both the HTS and the LTS reaction 14–16.…”
Section: Introductionmentioning
confidence: 99%